(untitled) (Notes in Current Biology, 2016)
The results of ecological analysis of the Carex bohemica Schreb. (Cyperaceae Juss.) flora of Ukraine using H. Ellenberg’s ecological scales and Y. P. Didukh’s synfytoindikation scales are presented in this article. Sedge bohemica corresponds to ecological groups such as: hemi-continental, sub-mesotherms, sub-aridophytes, sub-criophytes, sub-heliophytes, hyhrofytes, hemi-hydrocontrastophiles, sub-acidophiles, semi-eutrophes, hemi-karbonatophobes, hemy-nitrophiles and sub-aerophobes. Taking into account the results of analysis of ecological parameters, it is determined that C. bohemica s stenotopical for climatic and edaphically ecological factors habitat. Ecological features of this species are presented by different tolerance ranges of scoring. These features show adaptation level of sedge bohemica to its occupied ecological nicheand can partially describe its rarity in Ukraine.